2020
DOI: 10.7717/peerj.9395
|View full text |Cite
|
Sign up to set email alerts
|

Doing nothing and what it looks like: inactivity in fattening cattle

Abstract: Background Animals kept in barren environments often show increased levels of inactivity and first studies indicate that inactive behaviour may reflect boredom or depression-like states. However, to date, knowledge of what inactivity looks like in different species is scarce and methods to precisely describe and analyse inactive behaviour are thus warranted. Methods We developed an Inactivity Ethogram including detailed information on the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…the low responsiveness of ‘withdrawn’ horses [11]). This would parallel similar, fruitful, investigations of the physical characteristics of welfare-significant inactivity by Fureix et al on horses [10,11], Hennessy et al on laboratory macaques [7,8], Hintze et al on cattle [85] and Meagher et al on mink [48,86]. The resulting refined ethograms could then enhance the validity and practical value of mouse IBA as a welfare indicator: important as these animals are used extensively in research, and their welfare is attracting growing scrutiny [87].…”
Section: Discussionsupporting
confidence: 60%
“…the low responsiveness of ‘withdrawn’ horses [11]). This would parallel similar, fruitful, investigations of the physical characteristics of welfare-significant inactivity by Fureix et al on horses [10,11], Hennessy et al on laboratory macaques [7,8], Hintze et al on cattle [85] and Meagher et al on mink [48,86]. The resulting refined ethograms could then enhance the validity and practical value of mouse IBA as a welfare indicator: important as these animals are used extensively in research, and their welfare is attracting growing scrutiny [87].…”
Section: Discussionsupporting
confidence: 60%
“…Dairy calves' play behavior is easy to recognize, it can be measured noninvasively and it is a cause and, at the same time, a consequence of good welfare [16,32]. Therefore, to improve the wellbeing of these mammals, play behavior should be allowed to be expressed to a greater extent, by ensuring a more gradual cow-calf separation and/or larger pens to keep calves together, ensuring them an adequate environmental and social stimulation [24]. For the present study, we excluded some behaviors reported as possible play behaviors [11,22]: head shaking, rubbing or scratching, ear flicking, tail swishing, quick transition from standing to lying and vocalization, because those behaviors could be also markers of stress or pain [32,43,[57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Locomotor play emerges a few hours after birth, but newborn dairy calves are usually placed in individual pens, where they remain up to 8 weeks of age [23]. The percentage of inactive calves is higher on intensive farms than both pasture and semiintensive farms [24], because the lack of stimuli and, in particular, the deprivation of maternal care and social contacts may compromise the animal welfare and consequently the expression of locomotor activity [25].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of behavioral response to novel or unexpected stimulation may indicate a break-down in attentional processes arising from housing in impoverished environments (Wemelsfelder, 1991) and this lack of arousal can be an indicator of boredom (Burn, 2017). The fact that calves of the "inactive" personality tended to also show reduced activity in the home pen (measured using motion index and steps from accelerometers) may further support inactivity as a reflection of boredom in these calves (Hintze et al, 2020). Consequently, redirected behaviors toward immediately available stimuli in the housing environment may arise from a need to 'do something' (Wemelsfelder, 1993) and we suggest this may have manifested in more non-nutritive oral behaviors in calves of the "inactive" personality.…”
Section: Personality and Feeding Behaviorsmentioning
confidence: 91%